2010
DOI: 10.1021/tx1002595
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Partition-Controlled Dosing System for Cell Assays

Abstract: Hydrophobic and volatile chemicals have proven to be difficult to dose in cell assays. Cosolvents are often needed to dissolve these chemicals in cell culture medium. Moreover, the free concentration of these chemicals in culture medium may diminish over time due to metabolism, evaporation, and nonspecific binding to well plate surfaces and serum constituents. The aim of this study was to develop a partitioncontrolled dosing system to maintain constant concentrations of benzo(a)pyrene, 1,2-dichlorobenzene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
1
75
0
Order By: Relevance
“…Smith et al (2010a) used glass test vessels cast with a layer of PDMS as a passive dosing reservoir for exposure of Daphnia magna. Kramer et al (2010) placed PDMS sheets on the bottoms of the wells of a 24-well plate, for exposure of fish cell lines that were grown on membranes of well plate inserts, and modelled free medium concentrations. Recently, two studies applied passive dosing for exposing zebrafish early life stages to HOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (2010a) used glass test vessels cast with a layer of PDMS as a passive dosing reservoir for exposure of Daphnia magna. Kramer et al (2010) placed PDMS sheets on the bottoms of the wells of a 24-well plate, for exposure of fish cell lines that were grown on membranes of well plate inserts, and modelled free medium concentrations. Recently, two studies applied passive dosing for exposing zebrafish early life stages to HOCs.…”
Section: Introductionmentioning
confidence: 99%
“…These include general toxicity in the Microtox bacterial assay [ 18 ], immunotoxic effects in human cell lines [ 9 ], cytotoxicity and EROD activity in rainbow trout cell lines [ 24 ], dioxin-like activity in the DR-Calux ® assay [ 25 ], as well as mutagenicity in the Ames II assay [ 23 , 26 ]. These studies have all shown the utility of passive dosing for providing rigorously defi ned and stable C Free exposure concentrations, leading to an increase in the apparent test sensitivity when compared to conventional solvent spiking [ 23 -26 ].…”
Section: Control Of Hydrophobic Compound Exposurementioning
confidence: 99%
“…Kramer et al [ 24 ] used 0.177 mL silicone disks to passively dose 1.7 mL medium, and Booij et al [ 25 ] cast 0.01-0.1 mL PDMS silicone into the base of culture wells for dosing 2 mL medium. For compounds with K Silicone/Free values below 1,000, the selection of a suitable ratio is more critical since the HOC mass distribution is shifted towards the aqueous phase, and reduced V Water / V Silicone ratios are needed to avoid depletion (see ( 2 )).…”
Section: Step 1: Selection Of a Passive Dosing Phasementioning
confidence: 99%
“…Since the freely available concentration usually is the driving force for kinetic processes, as well as toxic reactions on the (sub-) cellular level, these processes will influence the free concentration and thus the effect . It is therefore necessary to estimate or measure this free concentration, especially when it is expected that the free concentration will differ from the nominal concentration (on the basis of known physico-chemical properties such as lipophilicity) (Gülden and Seibert, 2003;Heringa et al, 2004;Kramer et al, 2010Kramer et al, , 2012.…”
Section: Biokinetic 2 Considerationsmentioning
confidence: 99%